The influence of gadget usage and maternal attachment on the cognitive and motor development of early childhood in Situbondo Regency - Damayanti, Findya; Supriyono, Supriyono (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The purpose of this study is to determine the effects of device use and maternal bonding on early childhood cognitive and motor development in Situbondo Regency. In this research, the sample used was 311 respondents using quantitative methods. The multiple linear regression analysis technique was carried out using SPSS version 22 software. The data collection technique used in this research was observation, interviews, filling out Google forms and also direct questionnaires. The results of this research show a partial contribution, namely between the use of gadgets on cognitive development in early childhood, there is a partial contribution, namely between maternal attachment to cognitive development in early childhood, then there is a partial contribution between the use of gadgets and motor development in early childhood. , while there is no partial contribution of maternal attachment to motor development in early childhood. The use of devices in early childhood requires care and supervision, and also the mother’s role in the operation, as overuse of the device by the child can lead to addiction to playing with the device. This negatively affects the child’s growth and development process, especially the development of cognitive and motor skills. Dependence on the use of gadgets hinders the child’s growth and development process. Keywords: Gadget Use, Maternal Attachment, Cognitive Development, Motor Development